Autonomous Learners: How Competency-Based Curriculum could Accelerate EFL at English Education Department - Jati Suryanto (University of Muhammadiyah Purwokerto, 2018)
This paper will explore the implementation of the Competency-Based Curriculum at the Department of English Education, Universitas Muhammadiyah Yogyakarta, in reaching the goal of creating autonomous learners. Autonomous Learner is the ultimate objective in teaching learning processes. It is the beginning of the long-life learning processes. By creating autonomous learners, the process of achieving better graduate quality will be more effective and efficient. To reach the goal of producing autonomous learners, the Department of English Education, Universitas Muhammadiyah Yogyakarta, focuses its curriculum on the graduate abilities in “thinking how to think” and “learning how to learn” through the Competency Based Curriculum.Competency-Based Curriculum (CBC) is the teaching learning planning which bases its objectives on the students’ competences. To achieve the ultimate goal of language learning the Department of English Education, Universitas Muhammadiyah Yogyakarta needs to choose the relatively most effective curriculum and method of teaching for the students. Therefore, the department chooses CBC that applies student centred learning (SCL) to achieve the autonomous learning model. The department also applies constructivism approach which enhance the students curiosity to accelerate the autonomous learning in the student centred learning.